Soil Carbon Dynamics of Transition to Pacific Northwest Cellulosic Ethanol Feedstock Production. Issue 1 (13th January 2015) - Kendall, Joshua R.A.; Long, Dan S.; Collins, Harold P.; Pierce, Francis J.; Chatterjee, Amitava; Smith, Jeffrey L.; Young, Stephen L.
Abstract : Cellulosic ethanol commercialization promises to produce energy from agricultural biomass. Available biomass depends on plant net primary productivity (NPP) and crop type, which maintain total soil organic carbon (TOC). Effect of crop‐type, residue removal, and NPP on ethanol yield and TOC levels were assessed by means of a three‐pool C model derived from long‐term soil incubation, acid hydrolysis, and curve fitting of a nonlinear regression model. A 2‐yr field study consisting of three input regimes (Low, Medium, or High NPP), three crops [corn ( Zea mays L.), wheat ( Triticum aestivum, L.), and switchgrass (SG, Panicum virgatum L., cv. Blackwell)], and two harvest levels [residue removed (R) or residue not removed (NR)] was conducted near Prosser, WA, USA. After 2 yr, ethanol yield of all crops were similar under Low NPP while ethanol yield of SG under Medium and High NPP was significantly greater than that of corn or wheat under the same NPP. Switchgrass significantly contributed to active [mean residence time (MRT) < 7 d] and resistant (MRT > 500 yr) soil C pools. Other crops had net zero or significantly reduced C pools. During a transition to cellulosic energy production, SG will contribute to soil C maintenance across a range of potential net productivity.